Anti‐Dermatophyte and Anti‐Malassezia Activity of Extracts Rich in Polymeric Flavan‐3‐ols Obtained from Vitis vinifera Seeds. (13th October 2016) - Simonetti, Giovanna; D'Auria, Felicia Diodata; Mulinacci, Nadia; Innocenti, Marzia; Antonacci, Donato; Angiolella, Letizia; Santamaria, Anna Rita; Valletta, Alessio; Donati, Livia; Pasqua, Gabriella
Abstract : Several human skin diseases are associated with fungi as dermatophytes and Malassezia. Skin mycoses are increasing and new alternatives to conventional treatments with improved efficacy and/or safety profiles are desirable. For the first time, the anti‐dermatophytes and the anti‐ Malassezia activities of Vitis vinifera seed extracts obtained from different table and wine cultivars have been evaluated. Geometric minimal inhibitory concentration ranged from 20 to 97 µg/mL for dermatophytes and from 32 to 161 µg/mL for Malassezia furfur . Dried grape seed extracts analyzed by HPLC/DAD/ESI/MS showed different quali–quantitative compositions in terms of monomeric and polymeric flavan‐3‐ols. The minimal inhibitory concentrations for Trichophyton mentagrophytes and for M. furfur were inversely correlated with the amount of the polymeric fraction ( r = −0.7639 and r = −0.7228, respectively). Differently, the antifungal activity against T. mentagrophytes was not correlated to the content of flavan‐3‐ol monomers ( r = 0.2920) and only weakly correlated for M. furfur ( r = −0.53604). These results suggest that extracts rich in polymeric flavan‐3‐ols, recovered from V. vinifera seeds, could be used for the treatment of skin fungal infections. Copyright © 2016 John Wiley & Sons, Ltd.